The GARCH and volume relationship with heteroscedasticity in stock returns on the Jamaica stock exchange - Hamilton, Jacqueline ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Investigates the GARCH effect in the returns of three of the companies listed on the Jamaica Stock Exchange.